Heat Transfer in Rotor/Rotor and Rotor/Stator Cavity: Physics, Correlations and Numerical Modeling - Kielczewski, Kamil; Tuliszka-Sznitko, Ewa (Proceedings in applied mathematics and mechanics, 2013)
The transitional and turbulent flow in the near wall sublayer is now mostly modeled based on the existing knowledge of simple 2D flows. To determine the effect of three dimensionality on the turbulent flow structures and turbulent heat transfer in the near wall areas the authors investigate numerically (SVV) turbulent flow in rotor/stator and rotor/rotor flows (with and without axial throughflow). These simple model flows contain most of the phenomena that are needed to understand more complex, 3D transitional and turbulent flows. Attention is focused on the turbulent characteristics which should have more universal character. To stabilize calculations for high Reynolds numbers (up to Re=800 000) the SVV operator is introduced into the Navier‐Stokes and energy equations solver for cylindrical coordinate system without using complex numbers. Code optimization and parallelization have speeded up computations 20 times. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)